2009
DOI: 10.5539/jsd.v1n2p39
|View full text |Cite
|
Sign up to set email alerts
|

UrusSisa: An Intelligent System for Integrated Solid Waste Management

Abstract: UrusSisa is an expert system for selecting and designing solid waste technology. It can improve the process of selecting the best solid waste technology, and to make the knowledge of preliminary design of solid waste technology available. Knowledge based of UrusSisa consists of priority ranking using Analytical Hierarchy Process (AHP), and preliminary design of recommendation technology. AHP involves structuring multiple choice criteria into a hierarchy, assessing the relative importance of these criteria, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In Malaysia, it has been reported that the public is resistant to incineration as a result of its awareness of environmental pollution and the high operating costs that can result from using this technology (Manaf, Basri, & Basri, ). This underscores the need for a combination of options instead of the use of a single solid waste management option.…”
Section: Discussion Of Decision‐making Processmentioning
confidence: 99%
“…In Malaysia, it has been reported that the public is resistant to incineration as a result of its awareness of environmental pollution and the high operating costs that can result from using this technology (Manaf, Basri, & Basri, ). This underscores the need for a combination of options instead of the use of a single solid waste management option.…”
Section: Discussion Of Decision‐making Processmentioning
confidence: 99%
“…In addition to being the most frequent in the literature, environmental criteria are also the ones with the most sub-criteria (Figure 6), which are often not clearly and systematically selected (Manaf, Basri, & Ahmad, 2009). Some of these sub-criteria are strongly related to technical criteria, such as the waste reduction capacity or the energy recovery efficiency of the studied alternatives.…”
Section: Analysis Of the Criteria Involved In Mswmmentioning
confidence: 99%
“…The high frequency of the sub-criterion "Pollution of water resources" (33%) may be attributed to one of the main environmental impacts of the dump or landfill through the pollution of groundwater and surface water. All of these sub-criteria represent some form of environmental impact, which can be summarized as an "ecological impact" sub-criterion (Soltani, Sadiq, & Hewage, 2015;Kharat, Raut, Kamble, Kamble, 2016;Thampi & Rao, 2015;Nixon, Dey, Ghosh, & Davies, 2013;Manaf, Basri, & Ahmad Basri, 2009).…”
Section: Figure 6 Number Of Subcriteriamentioning
confidence: 99%
“…This led to objections and protests from affected communities. One of such a case is the protest against the installation of an incinerator in Selangor Malaysia [11]. To involve all stakeholders in the waste management decision making process, researchers have used various techniques or models [1,12].…”
Section: Introductionmentioning
confidence: 99%